PTH-017 Strategy for Colorectal Cancer (CRC) Screening in Individuals with Significant Co-Morbid Conditions. (4th June 2013) - Ramaraj, R; Dixon, R; Adams, H; Dolwani, S
Abstract : Introduction: With the advent of the Bowel cancer screening programme (BCSP) in the UK participants who have positive FOB tests are generally offered optical colonoscopy (OC) if considered safe, for early detection and prevention of CRC. In our study we undertook Computed Tomographic Colonography (CTC) in our hospital as the investigation of choice in those FOBt positive individuals with an American Society of Anesthesiology (ASA)grade > = 3 and analysed outcomes. Methods: Cases were prospectively discussed with screening practitioners carrying out assessments prior to OC and on the basis of hospital records and liaison with primary care physicians were assigned to CTC/OC with majority proceeding to OC as per standard practise. Patient data was accessed from our database in radiology, endoscopy and histology retrospectively and ASA grade assigned on the basis of the above information.44/69 cases that were referred for CTC from the BCSP between Feb 2009 and Nov 2011, were considered to have an ASA > = 3.CTC results were analysed and correlated with endoscopic and histological findings. Results: Out of 44 cases (17 female, 27 male, mean age 65.4) with positive FOBt referred for CTC in the BCSP, 50%(22) of patients had positive findings i.e.18 polyps and 4 suspected CRC.3/44 cases had a normal Flexible Sigmoidoscopy (FS) before CTC. Hence 41 of the above were considered to have had a primary CTC.44% (18/41) of patients referred for primary CTC had an endoscopy (20% OC, 24% FS), of which 61% had a polypectomy.41 primary CTCs detected 32 polyps in 18 cases and 4 cancers.18 cases (4 diminutive polyps on CTC not requiring OC/FS) underwent endoscopy as a result of the above (OC 8, FS 10) detecting 36 polyps (35 removed) in 11 patients.86% of polyps were detected on the left side and the majority of this (83%) were histologically confirmed to be adenomas. In addition to this 2 left sided cancers was confirmed endoscopically. Conclusion: In this small cohort CTC seems comparable to colonoscopy for detection of polyps and cancers1.In the patient group selected almost 44% of cases thought to have significant comorbidity who had primary CTC ended up having a lower GI endoscopy along with a need for therapy. It is also noted that the majority of significant polyps and all cancers were located in the left colon. We suggest that in this group a larger study evaluating a combination of CTC with FS (with no or minimal sedation) would be most appropriate in the context of the BCSP. It may also be useful to have evidence based criteria on fitness for colonoscopy in order to inform individuals and programmes on the appropriateness of screening in the context of comorbidity and the risk to benefit ratio. Disclosure of Interest: None Declared. Reference: Laghi, A et al . Current status on performance of CTC and clinical indications. EJR.doi:10.1016/j.ejrad.2012.05.026